Board Structure in State-Owned Enterprises (SOEs): Two-tier Model Analysis on the Implementation of Corporate Governance in Indonesia - Umanto, Umanto; Sri Hartantiningsih, Ika; Ikasari, Novita (UI Scholars Hub, 2022)
The discussion on corporate governance is focused on the duties of the board of commissioners (BOC). This is important, especially for countries that use the two-tier board model, such as Indonesia. This qualitative study aims to analyze the fulfillment of the number and composition of commissioners as well as the process of appointment and dismissal of commissioners in state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange. The results showed that BUMN had fulfilled the number and composition of commissioners. In addition, the existence of an audit committee and board of commissioner meetings is a component that plays an important role in assisting the commissioners in carrying out their supervisory functions. In the end, the process of succession of commissioners becomes an important part that affects the fulfillment of the number and composition.